Impact of body mass index on treatment efficacy of mirabegron for overactive bladder in females. (January 2016) - Krhut, Jan; Martan, Alois; Zachoval, Roman; Hanuš, Tomáš; Švabík, Kamil; Zvara, Peter
Abstract: Objective: Conclusive data comparing treatment efficacy of OAB pharmacotherapy in normal weight versus obese patients are not available. Obesity represents a risk factor for OAB/LUTS. We hypothesized that the effect of treatment with mirabegron might be diminished in obese patients. Study design: One hundred sixty nine women were prescribed mirabegron, 50 mg/day. Subjective and objective parameters were compared prior to and following three months of treatment. The study population was stratified into three groups according to a patients' BMI (A-normal weight, B-overweight, C-obese). We compared the change in parameters before and after treatment within each group. Subsequently the differences between groups were correlated. The same analysis was performed separately in patients who failed anticholinergic therapy ( n  = 85). A paired t -test was used to compare the parameters before and after the procedure within groups, and a two-sample t -test was applied to conduct a comparison between groups. A p value of <0.05 was considered statistically significant. Results: Significant improvement ( p  < 0.001) within all groups was observed in all parameters, with an exception in the number of severe urgency episodes per 24 h ( p  = 0.291) in Group B. We did not observe any statistically significant difference between groups A, B and C. The same trend has been observed in subgroup of patients, who did not respond previous antimuscarinic treatment. Conclusions: This study provides evidence in support of previously documented data indicating good efficacy of mirabegron in the treatment of OAB. The data obtained do not confirm our hypothesis that the body weight influences the treatment outcome of mirabegron.